2015
DOI: 10.1016/j.dnarep.2014.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characterization of RecA variants that contribute to extreme resistance to ionizing radiation

Abstract: Among strains of Escherichia coli that have evolved to survive extreme exposure to ionizing radiation, mutations in the recA gene are prominent and contribute substantially to the acquired phenotype. Changes at amino acid residue 276, D276A and D276N, occur repeatedly and in separate evolved populations. RecA D276A and RecA D276N exhibit unique adaptations to an environment that can require the repair of hundreds of double strand breaks. These two RecA protein variants (a) exhibit a faster rate of filament nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 89 publications
1
30
0
Order By: Relevance
“…Although the filament nucleation process characterized in the studies by Piechura et al, is a much more composite process than a simple on-rate for DNA binding, it is still intriguing to note that a faster on-rate in a binding equilibrium process, in the absence of any offrate changes, would produce tighter binding (Kd = off-rate/on-rate). Likewise, the shorter filaments formed by the radiation-resistant EcRecA mutants [32], like the shorter filaments formed by DrRecA itself [6], mirror the intrinsically shorter free-filament formation by DrRecA suggested in the present study.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Although the filament nucleation process characterized in the studies by Piechura et al, is a much more composite process than a simple on-rate for DNA binding, it is still intriguing to note that a faster on-rate in a binding equilibrium process, in the absence of any offrate changes, would produce tighter binding (Kd = off-rate/on-rate). Likewise, the shorter filaments formed by the radiation-resistant EcRecA mutants [32], like the shorter filaments formed by DrRecA itself [6], mirror the intrinsically shorter free-filament formation by DrRecA suggested in the present study.…”
Section: Discussionsupporting
confidence: 63%
“…Although no direct binding experiments were performed, the radiation-resistance induced EcRecA D276 mutants found by Hsu et al, like DrRecA itself [6], exhibited both (1) faster filament nucleation on DNA and (2) shorter filament formation [32]. Although the filament nucleation process characterized in the studies by Piechura et al, is a much more composite process than a simple on-rate for DNA binding, it is still intriguing to note that a faster on-rate in a binding equilibrium process, in the absence of any offrate changes, would produce tighter binding (Kd = off-rate/on-rate).…”
Section: Discussionmentioning
confidence: 95%
“…Among many accessory proteins regulating homologous recombination, the Swi5-Sfr1 complex stimulates various stages of the process, including filament assembly and strand exchange (25,26,(28)(29)(30)(31)(32)(33)(34)(35). Here, we took advantage of previously developed singlemolecule TPM experiments (36)(37)(38) to monitor Rad51 nucleoprotein filament assembly in real time (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
“…These findings suggest that RecA-mediated DNA repair mechanisms may differ from one Deinococcus species to another. Piechura et al demonstrated that RecA mutations affecting the Asp residue at positions 276 (D276), D276A and D276N increase radiation resistance of E. coli mutant strains up to 3 kGy (Piechura et al 2015). Further studies should be performed to determine if mutations at equivalent sites on RAD51, the eukaryotic homolog of RecA, have a similar effect on radiation resistance.…”
Section: Proteins Involved In Genome Preservation and Dna Repair Mechmentioning
confidence: 98%